Anti-desertification efforts run into the sand - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Desertification affects more than 900 million people in 100 countries and in some, including many in Africa, it is the biggest single environmental, social and economic threat. The UN Environment Programme estimates the cost of desertification at...